2020
DOI: 10.5888/pcd17.200122
|View full text |Cite
|
Sign up to set email alerts
|

Time Spent Eating, by Immigrant Status, Race/Ethnicity, and Length of Residence in the United States

Abstract: What is already known on this topic? Obesity risk increases with time spent in the United States, and time spent in the United States is negatively associated with diet quality and positively associated with energy intake and consumption of pre-prepared or processed foods. What is added by this report? An understudied but potentially important mechanism to explain the change in eating behaviors of immigrants and their offspring is change in time spent in meal preparation and consumption. We present data on imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Both husbands and wives, irrespective of sex, were found to display significant health concordance with their partners in our study. Some previous studies concluded similar findings that suggested no sex specificity in spousal interdependency, whereas others documented discrepant findings that support sex differences, even though they were also inconclusive on which sex was more sensitive to spousal influence. For instance, some research indicated that husbands were more responsive to spousal chronic diseases than wives; in contrast, some indicated that wives were more susceptible to their husband’s illness, such as frailty, metabolic syndrome, and depression, than vice versa .…”
Section: Discussionmentioning
confidence: 93%
“…Both husbands and wives, irrespective of sex, were found to display significant health concordance with their partners in our study. Some previous studies concluded similar findings that suggested no sex specificity in spousal interdependency, whereas others documented discrepant findings that support sex differences, even though they were also inconclusive on which sex was more sensitive to spousal influence. For instance, some research indicated that husbands were more responsive to spousal chronic diseases than wives; in contrast, some indicated that wives were more susceptible to their husband’s illness, such as frailty, metabolic syndrome, and depression, than vice versa .…”
Section: Discussionmentioning
confidence: 93%
“…More research is needed to better understand the mechanisms linking the use of a smuggler and later health risks. Based on other studies of undocumented immigrants in the US, barriers to accessing healthcare and changes in health behaviors may be plausible mechanisms [5][6][7][8][9][23][24][25][26].…”
Section: Discussionmentioning
confidence: 96%
“…First, we were unable to determine how the length of marriage or cohabitation affected the reported association because we did not have such information. However, previous studies did not find significant associations between duration of marriage and spousal risk of diabetes . The interaction of the duration of marriage with the association requires further investigation.…”
Section: Discussionmentioning
confidence: 99%